Bias in estimated short sprint profiles using timing gates due to the flying start: simulation study and proposed solutions - Jovanovic, M. (Computer Methods in Biomechanics and Biomedical Engineering, 2024)
Short sprints are most frequently evaluated and modeled using timing gates. Flying start distance is often recommended to avoid premature timing system triggering by lifting knees or swinging arms. This results in timing system initiation not being aligned with the initial force application, which yields bias in estimated short sprint parameters. This simulation study aims to explore the effects of the flying start distance on bias and sensitivity to detect changes in short sprint parameters using three models: the contemporary No Correction model and two proposed Estimated time correction (Estimated TC), and Estimated flying distance (Estimated FD) models. In conclusion, both the Estimated TC and Estimated FD models provided more precise parameter estimates, but surprisingly, the No correction model provided higher sensitivity for specific parameter changes. Besides standardizing the sprint starting technique for the short sprint performance monitoring, practitioners are recommended to utilize and track the results of all three models.